Characteristics, Role of Social Media and Self Esteem of victims in Cyberbullying Cases in Indonesia - Hidayat, Dasrun; Nur, Risti; Saputri, Almauri; Lyndon, Novel; Gustini, Leili Kurnia (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
This study examines the characteristics, role of social media, and self-esteem of victims in cyberbullying cases in Indonesia, motivated by the growing phenomenon of bullying behavior on social media platforms. The research aims to analyze how these characteristics and the social environment influence the self-esteem of cyberbullying victims. The study employed a qualitative descriptive method, using purposive sampling to select 20 informants who have experienced cyberbullying, including children, adolescents, and adults in Bandung. Data were collected through in-depth interviews. The findings indicate that cyberbullying negatively impacts victims' self-esteem, leading to trauma, social isolation, and reduced confidence. This lack of self-esteem is influenced by the anonymity of perpetrators and the rapid spread of harmful content. The study also highlights that gender, age, and social environment significantly shape the victims' experiences. Negative emotional turmoil is a major reason for perpetrators to engage in cyberbullying. The results suggest that early prevention and intervention from parents or guardians are crucial. Families should prioritize creating a supportive environment to enhance the resilience of children exposed to cyberbullying. These insights can contribute to developing more effective strategies to reduce the impact of cyberbullying on victims.Keywords: cyberbullying, social media, self-esteem. AbstrakPenelitian ini mengkaji karakteristik, peran media sosial, dan harga diri (self-esteem) korban dalam kasus cyberbullying di Indonesia, yang dilatarbelakangi oleh meningkatnya fenomena perilaku perundungan di media sosial. Tujuan penelitian ini adalah untuk menganalisis bagaimana karakteristik dan lingkungan sosial mempengaruhi harga diri korban cyberbullying. Penelitian ini menggunakan metode kualitatif deskriptif, dengan pemilihan 20 informan yang pernah menjadi korban cyberbullying melalui teknik purposive sampling, mencakup anak-anak, remaja, dan dewasa di Kota Bandung. Data dikumpulkan melalui wawancara mendalam. Hasil penelitian menunjukkan bahwa cyberbullying berdampak negatif pada harga diri korban, menyebabkan trauma, isolasi sosial, dan penurunan rasa percaya diri. Rendahnya harga diri ini dipengaruhi oleh anonimitas pelaku dan penyebaran informasi yang cepat. Penelitian juga menemukan bahwa jenis kelamin, usia, dan lingkungan sosial memiliki pengaruh signifikan terhadap pengalaman korban. Gejolak emosi negatif menjadi alasan utama pelaku melakukan cyberbullying. Hasil ini mengindikasikan pentingnya pencegahan dan intervensi dini dari orang tua atau wali. Keluarga harus menciptakan lingkungan yang mendukung untuk meningkatkan ketahanan anak yang mengalami cyberbullying. Temuan ini dapat berkontribusi pada pengembangan strategi yang lebih efektif untuk mengurangi dampak negatif cyberbullying terhadap korban.Kata Kunci: cyberbullying, media sosial, self-esteem.